2021 IEEE International Symposium on Circuits and Systems (ISCAS) 2021
DOI: 10.1109/iscas51556.2021.9401330
|View full text |Cite
|
Sign up to set email alerts
|

Voltage Flip Efficiency Optimization of SSHC Rectifiers for Piezoelectric Energy Harvesting

Abstract: Harvesting energy from environments has been a promising approach to power ubiquitously distributed Internet of Things (IoT) devices. For harvesting kinetic energy with piezoelectric transducers, synchronized switch harvesting on capacitors (SSHC) rectifiers have been demonstrated to achieve high energy extraction performance without using any inductor. In previous studies, the switched capacitors in SSHC rectifiers are chosen equal to the inherent capacitance of the piezoelectric transducer (PT) to achieve go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The theoretical maximum voltage inversion efficiency in the SSHC circuit when C k = C p is shown in Table 1. Yue and Du [88] found that in the energy transfer process, when the voltage balance was reached, the remaining charge of the PZT when C k C p would be much smaller than that when C k = C p . When C k = 100C p , the relationship between the voltage inversion efficiency and the number of C k is shown in Table 2.…”
Section: Inductorless Energy Harvesting Interface Circuitmentioning
confidence: 99%
See 1 more Smart Citation
“…The theoretical maximum voltage inversion efficiency in the SSHC circuit when C k = C p is shown in Table 1. Yue and Du [88] found that in the energy transfer process, when the voltage balance was reached, the remaining charge of the PZT when C k C p would be much smaller than that when C k = C p . When C k = 100C p , the relationship between the voltage inversion efficiency and the number of C k is shown in Table 2.…”
Section: Inductorless Energy Harvesting Interface Circuitmentioning
confidence: 99%
“…The voltage drop of the diode on circuit conduction can be reduced under low output voltage conditions Inductorless interface circuit [86][87][88] -Bad × Small size, large number of capacitors, and troublesome switching control strategy continued Circuit Maximum output power Load adaptability Selfpowered Features SCEVI [89] 1.5/SECE Good ×…”
Section: Piezoelectric Energy Injection Circuitmentioning
confidence: 99%
“…Capacitor-based circuits applied to piezoelectric energy harvesting include the synchronized switch harvesting on capacitor (SSHC) [57], the flipping-capacitor rectifier (FCR) [58], and the split-phase flipping-capacitor rectifier (SPFCR) [59], which allow on-chip integration by avoiding the use of off-chip inductors.…”
Section: Capacitor-based Interfacementioning
confidence: 99%
“…E NERGY harvesting has emerged as an alternative solution to traditional batteries, which are often bulky and difficult to replace in wireless applications in the Internet-of-Things (IoT) [1], [2], [3], [4], [5]. Among energy-harvesting systems, piezoelectric energy harvesting (PEH) has been widely used in recent years due to its high power density and compatibility with CMOS technologies [1], [6], [7], [8], [9], [10]. It harvests vibration energy from environments and converts it into electrical energy with a piezoelectric transducer (PT).…”
Section: Introductionmentioning
confidence: 99%